2013
DOI: 10.1108/et-06-2013-0084
|View full text |Cite
|
Sign up to set email alerts
|

Development of entrepreneurial intention in higher education and the effect of gender – a latent growth curve analysis

Abstract: Purpose -The objectives of this study are threefold: first, to analyze the development of intentions of individuals over time; second, to explore potential gender differences in intention development; and third, to analyze the relatedness of the initial level and development of the antecedents of intentions to the initial level and the development of intentions. Design/methodology/approach -Ajzen's Theory of Planned behavior is applied. Longitudinal data were collected in the fall of 2010, 2011 and 2012 in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 66 publications
5
89
2
6
Order By: Relevance
“…In addition to the procedural remedy, a statistical remedy, Harman's single-factor test, was used to control for common method biases. This test is one of the most widely-used techniques, and one 109 that has been used in many studies (Back et al, 2014, Joensuu et al, 2013, Jones and Jayawarna, 2010, Kenny and Fahy, 2011, Kibler, 2013, Kuckertz and Wagner, 2010, Avlonitis and Salavou, 2007 to address the issue of common method variance (Podsakoff et al, 2003). After conducting an Exploratory Factor Analysis (EFA) from all items of all constructs and performance, a single factor just explains less than 20% percent of the variance (Avlonitis and Salavou, 2007), and no single factors accounts for most of the variance in these variables (Dada and Watson, 2013).…”
Section: Common Methods Biasmentioning
confidence: 99%
“…In addition to the procedural remedy, a statistical remedy, Harman's single-factor test, was used to control for common method biases. This test is one of the most widely-used techniques, and one 109 that has been used in many studies (Back et al, 2014, Joensuu et al, 2013, Jones and Jayawarna, 2010, Kenny and Fahy, 2011, Kibler, 2013, Kuckertz and Wagner, 2010, Avlonitis and Salavou, 2007 to address the issue of common method variance (Podsakoff et al, 2003). After conducting an Exploratory Factor Analysis (EFA) from all items of all constructs and performance, a single factor just explains less than 20% percent of the variance (Avlonitis and Salavou, 2007), and no single factors accounts for most of the variance in these variables (Dada and Watson, 2013).…”
Section: Common Methods Biasmentioning
confidence: 99%
“…Shinnar, Hsu, and Powell (2014) 42 found that among students in an entrepreneurship education course, entrepreneurial intention increases for men from the beginning to the end of the semester while it weakens for women. In contrast, Joensuu, Viljamaa, Varamaki, and Tornikoski's (2013) 44 results demonstrated that both women's and men's entrepreneurial intentions decreased from the beginning to the end of the semester. However, men had higher levels of entrepreneurial intentions initially and their intentions did not decrease as much as women's intentions did in the study.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, the academic year of the individual can also be a motivator. and Joensuu et al (2013) found that students that were closer to graduation were more likely to exhibit greater or lesser intentions to start their own businesses.…”
Section: Control Variablesmentioning
confidence: 98%
“…As it regards the control variables, age (e.g., Georgellis et al, 2005;), academic year (e.g., Joensuu et al 2013) andethnicity (e.g., Pushkarskaya, 2008;Agbim et al, 2013) Ethnicity which represented the students' tribal ethnicity was a categorical variable representing 4 ethnic groups: Kamba, Kikuyu, Luhya and Luo.…”
Section: Estimation Approach and Control Variablesmentioning
confidence: 99%